Rethinking food aid to fight AIDS - Kadiyala, Suneetha; Gillespie, Stuart (International Food Policy Research Institute, 2004)
"To fully realize the potential of food aid to reduce risk and to mitigate the impacts of HIV/AIDS, existing strategies and interventiuons need to be re-viewed using an HIV/AIDS lens." -- from Text